Teaching English overseas an introduction - McKay, Sandra L. (Sandra Lee) (Oxford University Press, 1992)
Looks at the way in which social, political, economic, and cultural factors can influence the language classroom. This book also contains practical suggestions on how to cope with the professional problems and misunderstandings which can occur in overseas contexts. It is useful for native-speaker teachers of English preparing to work overseas.